Young people about career - career perception in adolescence and early adulthood - Magdalena Piorunek (Maria Curie-Skłodowska University, Lublin, Poland, 2021)
Abstract   Introduction Research and observations highlight the multiplicity of career patterns in the culture of postmodern societies. This phenomenon is inextricably linked to the emergence of a new, opaque social order in which the socio-cultural situation forces the abandonment of the linear narrative of life. Research objectives The primary aim of the research was to characterize and describe the perceptions, views, evaluations and attitudes of young people regarding the postmodern career construct. They have been captured at two stages immediately preceding the transition: - from middle school education to high school and technical schools (15-16 year olds,  sample size 179 respondents) and - from higher education to the labour market (age range of respondents 20-30 years, sample size 223 respondents). Research method As part of the diagnostic survey the author's original questionnaire Career in Postmodern Reality has been applied. Only open-ended questions included within have been used, which allowed the respondents to speak freely, and then the answers were analyzed qualitatively.  Results The ways of perceiving and defining a career and associations connected with it were presented. Also categories of people who, according to youth at the stage of adolescence and early adulthood, successfully pursue careers, as well as catalysts and inhibitors of careers mentioned in the statements of young people were discussed. Conclusions A review of the respondents' narratives leads to the following insights, among others. For them, career means the following: • the need for achievements and successes, which are defined by others; the pattern of a career related to promotion, prestige and material gratification is most often evoked; • the need to make it public, to appear in the media world, in virtual space; • popularity and fame as an important component of a desired career; • the inability to defer gratification in the professional sphere; • perceiving dissonances in career development: on the one hand, valuing activity, creativity as catalysts for success, on the other hand, conformism, using patronage, connections; • attributing the responsibility for failures and difficulties in career development to the outside.